Synthesis of beta-Ag2Se from organo-selenium precursor and silver nitrate in DMF via simultaneous reduction of selenium and silver salt - Khanna, P. K.; Singh, N.; Charan, Shobhit; Patil, K. R. (Materials Letters, 2006)
Reaction of selenium powder and silver nitrate in aqueous N,N'-dimethylformamide (aq. DMF) leads to formation of silver selenide. Similar reaction with cycloalkeno-1,2,3-selenadiazole an organic compound of selenium upon thermolysis, also produces silver selenide. It is believed that DMF activates selenium and reduces silver salt via in-situ generated hydrogen ion simultaneously. Slightly broadened X-ray diffraction pattern for pure beta silver selenide (beta-Ag2Se) was observed. Scanning electron microscopy (SEM) indicated that the agglomerated particles could be in the range of about 100 to 200 nm in dimension. EDAX analysis showed non-stoichiometric elemental ratio between silver and selenium. It is found that the weight percent of Ag is slightly higher than Se. However, free amorphous selenium is also detected by XPS analysis when the product is made by use of elemental selenium. Thermal analysis (TGA) revealed a small (4%) weight loss due to the presence of organics or the solvent from the reaction medium. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; nano powder; noble metal chalcogenides; Semiconductor

One-step preparation of nanosized Ag-PdCo-powder and its alloy formation at low temperature - Khanna, P. K.; Singh, N.; Kulkarni, D.; Marimuthu, R.; Charan, Shobhit; Patil, K. R.; Jain, G. H. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2007)
Nano-sized silver-palladium co-powder has been synthesized from silver nitrate-palladium chloride by wet chemical method. The present experimental conditions are applied for the first time for Ag-Pd co-powders wherein sodium formaldehyde sulfoxylate (SFS) has been used as an external reducing agent to simultaneously reduce respective metal salts. SFS reduces the metal salts at room temperature thus prevents formation of bigger particles of the respective metals in co-powder. Powder X-ray diffraction measurements ( XRD) and Transmission electron microscopy ( TEM) suggest the formation of nano-sized Ag-Pd co-powder with particle diameter in the range of about 25 nm. SEM shows that the powder morphology changes with temperature. Heat treatment of 90: 10 (Ag:Pd) composition showed shift in XRD peaks indicating alloy formation of Ag/Pd at lower temperature. Thick-films generated by use of the co-powder resulted in Ag/Pd alloy at about 500 degrees C as confirmed by the XRD. Thermal analysis showed that Ag/Pd co-powders initially gain the weight due to oxidation followed by the weight loss.
Keywords: alloy; Chemical synthesis; nano-powder; noble metal; Transition Metal

Solid state synthesis and room temperature magnetic properties of iron phosphide nanoparticles - Singh, N.; Khanna, P. K.; Joy, Pattayil Alias (Journal of Nanoparticle Research, 2009)
Room temperature magnetic properties have been achieved for nano-crystalline iron phosphide synthesized from the direct solid state reaction of iron chloride and tri-octylphosphine (TOP). The magnetization continuously increased with higher magnetic fields, indicating a super-paramagnetic behavior. It is observed that room temperature magnetism is possible for the material showing antiferromagnetic nature at low temperatures. In the present synthesis, TOP acted as a source of phosphorus as well as a surfactant. X-ray diffraction (XRD) studies revealed that the black powder is a mixture of FeP and Fe(2)P. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed elongated as well spherical particles. Energy dispersion X-ray analysis (EDAX) confirmed a non-stoichiometric iron phosphide. Presence of TOP was confirmed by infra-red (IR) spectroscopy, and thermo-gravimetric analysis (TGA) indicated about 6% wt. loss due to presence of organics.
Keywords: Iron phosphide; Semiconductors; Solid state reaction; synthesis; XRD